The important of quality service towards customer satisfaction / Farazila Mohd Sani - Mohd Sani, Farazila (Faculty of Business and Management, 2001)
Since the Second World War, many economically developed countries have undergone a structural change moving away from agriculture based economy to an industrialized economy. Economists like Chenery observed that economic development of a country goes hand in hand with industrial development. As a country became industrialized, it also achieved higher standard of living and economic affluence. This is then followed by a higher demand for goods and services.